Characteristics of Tapai Talas Bogor (Colocasia esculenta) on Variation of Steaming and Fermentation Durations - Farikha Dwi Oktavia (Universitas Muhammadiyah Sidoarjo, 2020)
The aim of this research was to determine characteristics of tapai talas Bogor (Colocasia esculenta) on variation of steaming and fermentation durations. Raw material was used talas Bogor, yeast, and aquadest. Randomized block design (RBD) was conducted with two factors. The first factor was durations of steaming, P1 (20 minutes), P2 (30 minutes), and P3 (40 minutes) and second factor was durations of fermentation F1 (48 hours), F2 (54 hours ), and F3 (60 hours). Data was analyzed using analysis of variance and further test BNJ 5%. The results of the analysis from durations of steaming indicated that were significant effect on ethanol content, texture, and color (brightness) and duration of fermentation ha significant effect on ethanol content tapai talas Bogor. The best treatment was tape that made used 10 minutes steaming and 60 hours of fermentation which shows 77.55 brightness, 70,00% water content, 3.51% ethanol content, 0.50 mg / ml reduction sugar, pH 4, 57, lactic acid content 0.03%, texture 1.10 x 105 pa. Water content of tapai talas Bogor still quite high that further processing was needed in order to extend shelf life and product diversification.